Synthesis, In-Vitro Evaluation, and Computational Investigation of Salicylic Hydrazide Derivatives as Potential Tyrosine Kinase–Targeted Anticancer Agents - Sulistyowaty, Melanny; Tri Widiandani; Albertus Aditya Setiawan; Seow Lay Jing; Neny Purwitasari; Ferlinahayati; Dwi Setyawan; Galih Satrio Putra; Anastasia Wheni Indrianingsih (Science and Technology Indonesia, 2026)
A series of N2-acyl salicylic hydrazides (S2-S6) and N-(substituted benzylidene) salicylic hydrazides (S7-S9) were synthesized from 2-hydroxybenzohydrazide (S1), using both microwave irradiation and conventional methods, and tested for its in vitro anticancer activity against human lung cancer cell, A549. The salicylic hydrazides were successfully synthesized in good yields (79–98%) and the in-vitro study results indicated that 3,4-dichloro-N'-(2-hydroxybenzoyl)benzohydrazide (S5) was most active among the tested compounds (IC50 value of 68.75 µM). In this work, we applied an integrated approach combining network pharmacology and computational analysis to explore how salicylic hydrazide derivatives affect tyrosine kinase–related pathways. The in-silico findings were in agreement with the in vitro results, indicating that compound S5 produced a docking score of –6.53468 kcal/mol. The findings of this research are expected to support further development toward identifying promising anticancer drug candidates derived from salicylic hydrazide derivatives.